MASKULINISASI IKAN CUPANG (Betta sp.) MENGGUNAKAN MADU ALAMI MELALUI METODE PERENDAMAN DENGAN KONSENTRASI BERBEDA - Muhamad Arasyidin Lubis; Muslim .; Mirna Fitrani (Universitas Sriwijaya, 2017)
ABSTRACT The use of natural honey in the process of Betta fish masculinization are expected to reduce the concentration of estrogen hormone and increase the testosterone. The purpose of this research is to determine the effect of natural honey to the percentage of the male betta fish by masculinization. This study has been conducted at the Aquaculture Laboratory, Faculty of Agriculture, Sriwijaya University. This study use a completely randomized design with 4 treatments and 3 replications. The treatment in this research was betta fish larvae aged 5 days that submersed on natural honey media with different concentration for 12 hours. The treatment were the addition of natural honey as much as 4 ml/L (P1), 5 ml/L (P2), 6 ml/L (P3), 7 ml/L (P4) and without natural honey addition as control (P0). Parameters observed consist of percentage of betta fish male, survival rate and quality of water. The result of this research shows that the addition of natural honey with difference concentration has significant effect to male betta fish percentage. Treatment P2 with concentration 5 ml/L is the best result, it produced 77.33% of male betta fish after immersion for 12 hours. Keywords : Betta fish (Betta sp.), Masculinization, Natural honey